2017
DOI: 10.32831/jik.v3i1.39
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Pengetahuan Dengan Sikap Ibu dalam Pemberian ASI Eksklusif di Wilayah Kerja Puskesmas Pranggang Kabupaten Kediri

Abstract: Exclusive breastfeeding is breast-feeding for 6 months without any additional liquid. According to Health Department of Kabupaten Kediri in 2013, the exclusive breastfeeding program’s achievement is 57.2%. The lowest or the worst achievement of exclusive breastfeeding in Kediri is in Public Health center of Pranggang, it is 5.4%. The purpose of this study is to identify and analyze the correlation between mother’s knowledge and attitude in giving exclusive breastfeeding at territorial of Public Health in Prang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 0 publications
1
3
0
7
Order By: Relevance
“…These results are in line with research conducted by Yanuarini (2014) in the working area of the Pranggang Health Center in Kediri Regency, it was found that most respondents had very good attitudes in exclusive breastfeeding, namely (72.92%). This result is also the same as the research conducted by Agow et al (2017) in the work area of the Small Motoboi Community Health Center in Mobagu City, getting p = 0.148> 0.05, which means that the mother's attitude is not related to exclusive breastfeeding.…”
Section: Attitudessupporting
confidence: 89%
See 2 more Smart Citations
“…These results are in line with research conducted by Yanuarini (2014) in the working area of the Pranggang Health Center in Kediri Regency, it was found that most respondents had very good attitudes in exclusive breastfeeding, namely (72.92%). This result is also the same as the research conducted by Agow et al (2017) in the work area of the Small Motoboi Community Health Center in Mobagu City, getting p = 0.148> 0.05, which means that the mother's attitude is not related to exclusive breastfeeding.…”
Section: Attitudessupporting
confidence: 89%
“…Information can be found in everyday life obtained from data and observations of the surrounding environment. As well as information obtained from both formal and non-formal education (Yanuarini, 2014).…”
Section: Multivariate Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The attitude about exclusive breastfeeding by respondents is a factor that determines a person's willingness or readiness to give exclusive breastfeeding [15]. In this study, respondents who had the wrong knowledge about exclusive breastfeeding or believed certain myths which ultimately formed a negative attitude.…”
Section: Discussionmentioning
confidence: 89%
“…Penelitian ini kurang sejalan dengan banyak penelitian lainnya yang menyatakan bahwa ada hubungan antara pengetahuan ibu dengan pemberian ASI eksklusif. [10][11][12][13][14][15] Hasil penelitian ini sejalan dengan teori Roesli, (2010), yang menemukan bahwa makanan bagi bayi terutama 6 bulan pertama adalah ASI, tidak ada yang bisa menggantikan nutrisi ASI bagi bayi, semahal apapun susu formula. 5 ASI unik karena setiap ibu akan menghasilkan ASI yang berbeda, sesuai dengan kebutuhan bayinya.…”
Section: Pembahasanunclassified